Imam Baghawi’s Masabih Al-sunnah and Azerbaijani Hadith Scholars - Ismayilov, Gulagha (Scholarya Demo Journal of Ruby, 2019)
It is known that Azerbaijanis are the first nation after the Arabs to massively convert to Islam. The emergence of a religious union not only strengthened the political integrity of Azerbaijan, but also served as a factor in scientific and cultural progress. Along with the works on secular sciences, works on Islamic sciences appeared after the spread of Islam in the geographical points of this religion. Especially many works have been written about fiqh, hadith, tafseer and other fileds related to Sharia which became more important due to the spread of Islam in the larger areas. Beginning in the early periods, this work gained wider scope in later periods. Several works were written on hadith which is considered one of the two major sources of Sharia sciences. One of these works is Imam Baghawi’s Masabih al-Sunnah, which occupies a special place in the history of Islam. This work was also one of the main sources for the emergence of many works of this kind. Memorizing, teaching and commenting on this work by many hadith scholars (muhaddiths) reveals the importance of this work. One of the main factors that attract our attention is the role of this work among medieval Azerbaijani hadith scholars. We can mention the names of several scholars to show the significance of this work among the Azerbaijani authors. Valiaddin Khatib al-Tabrizi is the major one who was the leading scholar in the field of hadith, fiqh, tafseer and other Islamic sciences. His actual name was Muhammad ibn Abdullah Al-Umari al-Tabrizi and wrote with the penname of Valiaddin Khatib al-Tabrizi. Valiaddin Tabrizi added comments to Imam Baghawi’s Masabih in and named his book Mishkat al-Masabih. Another well-known Azerbaijani hadith scholar, Allam Tajaddin Abul Hasan Ali ibn Abdullah ibn Abu Bakr Ardabili who familiarized himself with Imam Baghawi’s Sharh al-Sunnah and Al Masabih thanks to his teacher Sheikh Fahraddin Jarullah al-Jandarani. The article also provides brief information about some other hadith scholars such as Shamsaddin Muhammad ibn Muzaffar Khalkhali, Allam Hussein ibn Hassan al-Husseini Khalkhali, Sheikh Badruddin Muhammad Ardabili, Kazi Imadaddin Ahmed, Qari Ibrahim ibn Ahmad etc. and the names of their works are listed.